Making the UN Ocean Decade work? The potential for, and challenges of, transdisciplinary research and real‐world laboratories for building towards ocean solutions. Issue 1 (4th December 2022) - Franke, Andrea; Peters, Kimberley; Hinkel, Jochen; Hornidge, Anna‐Katharina; Schlüter, Achim; Zielinski, Oliver; Wiltshire, Karen H.; Jacob, Ute; Krause, Gesche; Hillebrand, Helmut
Abstract: Due to the strong interconnectedness between the ocean and our societies worldwide, improved ocean governance is essential for sustainable development in the context of the UN Ocean Decade. However, a multitude of different perspectives—ecological, societal, political, economic—and relations between these have to be understood and taken into consideration to foster transformative pathways towards marine sustainability. A core challenge that we are facing is that the 'right' response to complex societal issues cannot be known beforehand as abilities to predict complex systems are limited. Consequently, societal transformation is necessarily a journey towards the unknown and therefore requires experimental approaches that must enable the involvement of everyone with stakes in the future of our marine environment and its resources. A promising transdisciplinary research method that fulfils both criteria—being participatory and experimental—are real‐world laboratories. Here, we discuss how real‐world labs can serve as an operational framework in the context of the Ocean Decade by facilitating and guiding successful knowledge exchange at the interface of science and society. The core element of real‐world labs is transdisciplinary experimentation to jointly develop potential strategies leading to targeted real‐world interventions, essential for achieving the proposed 'Decade Outcomes'. The authors specifically illustrate how deploying the concept of real‐world labs can be advantageous when having to deal with multiple, overlapping challenges in the context of ocean governance and the blue economy. Altogether, we offer a first major contribution to synthesizing knowledge on the potentials of marine real‐world labs, considering how they act as a way of exploring options for sustainable ocean futures. Indeed, in the marine context, real‐world labs are still under‐explored but are a tangible way for addressing the societal challenges of working towards sustainability transformations over the coming UN Ocean Decade and beyond. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Auszug: Der Mensch hat in vielerlei Hinsicht einen starken Einfluss auf die Ozeane, was insbesondere die Verbesserung von ‚Ocean Governance' für einen nachhaltigen Schutz und Nutzen der Ozeane notwendig macht. Hierfür müssen unterschiedliche Aspekte—ökologische, gesellschaftliche, politische and wirtschaftliche—und die Beziehungen zwischen ihnen verstanden und berücksichtigt werden, wozu die derzeitige UN Ozeandekade einen passenden Rahmen bietet. Eine der zentralen Herausforderungen mariner Nachhaltigkeit und Transformation besteht darin, dass die ‚richtige' Lösung komplexer gesellschaftlicher Probleme nicht im Voraus bekannt sein kann. Dementsprechend ist unsere Fähigkeit zu prognostizieren, wie sich marine sozial‐ökologische Systeme zukünftig entwickeln könnten, begrenzt. Dadurch ist ein gesellschaftlicher Wandel in Richtung Nachhaltigkeit zwangsläufig eine Reise ins Ungewisse und erfordert daher experimentelle Ansätze, die die Beteiligung aller Interessenvertreter/innen sicherstellt. Eine vielversprechende transdisziplinäre Forschungsmethode, die nicht nur Partizipation, sondern auch gemeinsames Experimentieren und Evaluieren ermöglicht, sind Reallabore. In unserem Artikel erörtern wir wie marine Reallabore im Rahmen der Ozeandekade als wichtiges Werkzeug dienen können, indem sie den Austausch von Wissen und Erfahrung an der Schnittstelle von Forschung und Gesellschaft ermöglichen. Das Kernelement von Reallaboren ist transdisziplinäres Experimentieren, um gemeinsam nachhaltige Strategien zu entwickeln, die zu Interventionen in der Praxis führen und somit helfen die Ziele der Ozeandekade zu erreichen. In unserem Artikel veranschaulichen wir insbesondere, wie die Anwendung des Reallaborkonzepts von Vorteil sein kann, wenn es darum geht, sich mit verschiedenen, sich überschneidenden Herausforderungen im Zusammenhang von ‚Ocean Governance' und ‚Blue Economy' zu befassen, um über geeignete Schutz‐ und Nutzungsstrategien zu entscheiden. Insgesamt liefern wir eine Synthese zu den Potenzialen von marinen Reallaboren, indem wir untersuchen, wie sie als Mittel zur Erforschung von Optionen für den nachhaltigen Schutz und Nutzen der Ozeane dienen können. Bisher wurden Reallabore im marinen Kontext wenig angewendet, obwohl sie ein vielversprechendes Werkzeug darstellen, um gesellschaftliche Herausforderungen zu bewältigen, die sich im Rahmen von Nachhaltigkeitstransformationen während der UN Ozeandekade und darüber hinaus ergeben.